Paraphilias: an update on nosology and diagnostic challenges - Sahoo, Swapnajeet (The journal of forensic psychiatry & psychology, 2023)
Ever since the inception of paraphilias in the psychiatric nosological system, it has been in several controversies ranging from determining normal sexual behaviour from abnormal, role of culture, diagnosing paraphilia as deviant sexual behaviour and various medico-legal issues related to sexual offenders and predators. Over the years, several landmark changes have been made in the subsection of paraphilias in both DSM and ICD nosological system. The evolutionary journey of paraphilias to paraphilic disorder is remarkable, yet there are various unresolved issues related to its nosological status and diagnosis. To review some fundamental concepts of paraphilias related to its evolution in nosological systems and discuss its various diagnostic and medico-legal/forensic issues. A comprehensive literature search was conducted on paraphilias in PubMed and Google Scholar and through the cross-references of relevant articles till June 2022. Keywords included ‘paraphilias,’ ‘nosology,’ ‘critique’ ‘issues’ and ‘diagnosis’ in various combinations. Only original articles (abstract and full text), review articles, viewpoint articles and recommendations published in English, till June 2022, were reviewed and checked thoroughly. Articles published in non-English languages were excluded. 34 articles related to the topic were found, including those relevant to paraphilias’ nosology and diagnostic issues. We discuss in detail the nosological journey of paraphilias and various controversies related to it. Additionally, we discuss the various diagnostic and forensic issues. From our review, we conclude that the most valid indicators of true paraphilic disorders i.e. exclusiveness, fixation and compulsiveness, which are the most complex entities to establish in a forensic context, are not adequately addressed even by the new criteria of DSM-5 and ICD-11 of paraphilic disorders. Hence, even after so many modifications, paraphilic disorders still present challenges to our conceptualization of mental disorders.